Looking Beyond Fibrillar Features to Scale Gecko-Like Adhesion - Bartlett, Michael D.; Croll, Andrew B.; King, Daniel R.; Paret, Beth M.; Irschick, Duncan J.; Crosby, Alfred J. (Advanced materials (Weinheim), 2012)
Hand‐sized gecko‐inspired adhesives with reversible force capacities as high as 2950 N (29.5 N cm‐2) are designed without the use of fibrillar features through a simple scaling theory. The scaling theory describes both natural and synthetic gecko‐inspired adhesives, over 14 orders of magnitude in adhesive force capacity, from nanoscopic to macroscopic length scales.